Resenha de LEBNER, Ashley (ed.). 2017. Redescribing Relations: Strathernian Conversations on Ethnography, Knowledge and Politics. New York: Berghahn Books - Maciel, Lucas da Costa (Revista de Antropologia da UFSCar, 2021)
Resenha de Lebner, Ashley (ed.). 2017. Redescribing Relations: Strathernian Conversations on Ethnography, Knowledge and Politics. New York: Berghahn Books.